2018
DOI: 10.1016/j.cub.2018.05.094
|View full text |Cite
|
Sign up to set email alerts
|

AMPK-Mediated BECN1 Phosphorylation Promotes Ferroptosis by Directly Blocking System Xc– Activity

Abstract: Ferroptosis is a form of regulated cell death triggered by lipid peroxidation after inhibition of the cystine/glutamate antiporter system X. However, key regulators of system X activity in ferroptosis remain undefined. Here, we show that BECN1 plays a hitherto unsuspected role in promoting ferroptosis through directly blocking system Xc activity via binding to its core component, SLC7A11 (solute carrier family 7 member 11). Knockdown of BECN1 by shRNA inhibits ferroptosis induced by system X inhibitors (e.g., … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
383
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 535 publications
(433 citation statements)
references
References 50 publications
12
383
2
Order By: Relevance
“…These results are consistent with the previous observations that the phosphorylation of Beclin 1 at Ser90/93 (Fogel et al , ) or monophosphorylation of Beclin 1 at Ser90 (Wei et al , ; Fujiwara et al , ; Li et al , ) positively regulates autophagy. It should be noted that some studies found an autophagy‐independent role for Beclin 1 phosphorylation at Ser90/93/96 by AMPK, which enables Beclin 1 to interact with SLC7A11 and initiate ferroptosis, a type of programmed cell death (Song et al , ). The basis for whether Beclin 1 phosphorylation triggers autophagy or ferroptosis remains unknown, but could relate to the intensity or duration of the perturbation.…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with the previous observations that the phosphorylation of Beclin 1 at Ser90/93 (Fogel et al , ) or monophosphorylation of Beclin 1 at Ser90 (Wei et al , ; Fujiwara et al , ; Li et al , ) positively regulates autophagy. It should be noted that some studies found an autophagy‐independent role for Beclin 1 phosphorylation at Ser90/93/96 by AMPK, which enables Beclin 1 to interact with SLC7A11 and initiate ferroptosis, a type of programmed cell death (Song et al , ). The basis for whether Beclin 1 phosphorylation triggers autophagy or ferroptosis remains unknown, but could relate to the intensity or duration of the perturbation.…”
Section: Discussionmentioning
confidence: 99%
“…Next, we would like to understand how AMPK/SREBP1 is activated by ferroptosis inducers. As AMPK is a promoter of autophagy and ferroptosis is an autophagic cell death process called ferritinophagy (Gao, Monian et al, 2016, Song, Zhu et al, 2018, we asked whether ferritinophagy is involved in AMPK activity. Nuclear receptor coactivator 4 (NCOA4) was a selective cargo receptor for the selective autophagic turnover of ferritin .…”
Section: Ampk-srebp1 Pathwaymentioning
confidence: 99%
“…Thus, Beclin 1 phosphorylation by AMPK at S90, S93, S96 regulates ferroptosis, an iron-dependent cell death, upon binding to SLC7A11 (solute carrier family 7 member 11). Indeed, Beclin 1 overexpression or Tat-Beclin 1 treatment increases ferroptosis cell death and decreases tumor growth in vivo [60]. However, the direct effects of these serine phosphorylation events by AMPK require further investigation.…”
Section: Ampkmentioning
confidence: 99%